Adapting science education during crises: first lessons from the COVID-19 pandemic (Educational Dimension, 2020)
The COVID-19 pandemic has disrupted science education, forcing teachers and students to switch to online and hybrid modes of learning. This paper reviews recent research on how to cope with these challenges using various innovative teaching strategies. These include online platforms and tools, historical and philosophical perspectives, and holistic approaches to science education. The paper discusses the implications of these findings for the future of science education.